Case report: Acute vestibular syndrome and cerebellitis in anti-Yo paraneoplastic syndrome - Kherallah, Bassil; Samaha, Elias; Bach, Sarah E.; Guede, Cindy; Kattah, Jorge C. (Frontiers in Neurology, 2022)
Background: We define acute vestibular syndrome (AVS) as a sudden onset of vertigo, nausea, vomiting and head motion intolerance, more frequently associated with an acute peripheral, unilateral vestibulopathy. In 10-20% cases with a central vestibulopathy, stroke is the most frequent cause. We report three consecutive patients examined during the past decade, with an AVS, associated with downbeat nystagmus, dysarthria and progressive limb, and truncal ataxia Methods: All patients underwent neurologic examination, Video-Oculography, MRI, serum cancer markers, spinal fluid examination, paraneoplastic panel testing and oncologic workup. With a consolidated diagnosis of cancer/paraneoplastic syndrome, we treated with plasma exchange (PLEX), high-dose steroids, surgery, and oncologic investigation. We additionally provided oncotherapy in one out of three patients. Results: All three patients had an AVS on presentation, characterized by downbeat nystagmus (DBN), impaired horizontal and vertical pursuit, impaired VOR suppression, truncal and limb ataxia, and dysarthria. Vertigo, nausea, and vomiting subsided after several days, followed by ataxia and oscillopsia due to persistent DBN. All patients had lymphocytic pleocytosis and elevated protein in CSF and normal MRI brain. One patient had confirmed ovarian cancer with high CA 125 serum levels; another had undifferentiated cancer of unknown primary with high CA-125, and one with esophageal cancer. All had positive PCA -1 (anti-Yo) antibody titer. One patient with expeditious immunosuppression had slowed ataxia progression for 18 months, whereas the other two patients with delayed initiation of treatment had rapidly progressive ataxia. Discussion: Paraneoplastic encephalitis related to PCA-1 antibody targets Purkinje cells, and cells in the granular layer of the cerebellar flocculus, the midline uvula, nodulus, deep nuclei and lateral cerebellar cortex. Clinically the patients had an AVS characterized by DBN and progressive ataxia and unremarkable neuroimaging studies. Rapid initiation of treatment may offer a greater chance to prevent further neurological decline. An AVS, DBN and normal MRI should have prompt treatment with high-dose steroids and plasmapheresis, even prior to confirming final diagnosis, to mitigate the risk of rapidly progressive and irreversible neurologic decline. Inflammatory spinal fluid examination and serum oncogenic markers may lead to rapid identification of PCA-1 immunophenotype, confirmed by serum CSF Purkinje cell (PC) antibodies.